Predictable Mispredictions in the Context of Physical Activity and Sport: A Review. (December 2014) - Chatzisarantis, Nikos LD; Dimmock, James A; Jackson, Ben
<x xml:space="preserve">Abstract</x> Theoretical models and research that aim to identify antecedents of participation in physical activities or sport can measure antecedents of physical activity behaviour through instruments that involve subjective predictions. In this article, we argue that such instruments may not reflect physical activity experiences or behaviour accurately because people are not very good predictors of future states. Additionally, we propose that mispredictions may be predictable because they are "caused" by tendencies to neglect processes related to hedonic adaptation and competing alternatives. We also suggest that it may be possible to improve measurement of antecedents through methods that focus respondents' attention on factors that cause mispredictions or through experiential sampling methods.